Local government finance in Nigeria - Orewa, G. Oka.; Nigerian Institute of Social and Economic Research (Ibadan ; London : published for the Nigerian Institute of Social and Economic Research by Oxford U.P., 1966)
It provides broad practical information on the structure of local government finance in Nigeria,with some pointers to a number of problems associated with the system
Includes bibliographical references: p. [154]-156.
obn23/01/2019
Loans
Keywords: Local finance; Local government